IMPROVING STUDENTS’ READING COMPREHENSION THROUGH QAR (QUESTION AND ANSWER RELATIONSHIP) - Oktavia, Rina; Sutapa, Y.Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:  The aim of this study was to determine the effectiveness and evaluate how effective the use of QAR (Question and Answer Relationship) on improving the students' reading comprehension, especially on the Descriptive Text. In this study, the authors used a Class Action Research, while for collecting the data, the authors use the observation notes and some written test instruments to measure student progress. The results of the data analysis and observation notes, found that the effect of the QAR (Question and Answer Relationship) are influence at the level of students' understanding in  descriptive reading text, the  students were able to answer the question by searching the  information in text, and increasing their  motivation and most of student are interest in the subject English Basically, the student increasing in this study is varied, if we look at the graph of value increasing, perhaps only a few are able to improve his abilities, but on the other hand, the growing and respect for the English class is quite an increase, to cultivate a sense of curiosity towards English had already made his own pride for researchers.Keywords: QAR (Question and Answer Relationship), Reading Comprehension, Descriptive Text Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui keefektifan dan mengevaluasi seberapa efektifnya penggunaan QAR (Question and Answer Relationship) pada peningkatan pemahaman membaca siswa khususnya pada jenis Text Descriptive. Dalam penelitian ini, penulis menggunakan Penelitian Tindakan Kelas sedeangkan untuk menggumpulkan data, penulis menggunakan catatan obervasi dan beberapa intrumen test tertulis untuk mengukur kemajuan siswa. Hasil dari data analisis dan catatan observasi, penulis menemukan bahwa efek dari QAR (Question and Answer Relationship) berpengarauh pada tingkat pemahaman siswa terhadap text bacaan descriptive, siswa mampu menjawab pertanyaan dengan mencari informasi yang ada dalam text,  dan meningkatnya motifasi dan minat siswa pada pelajaran bahasa inggris. Pada dasarnya peningkatan siswa pada penelitian ini beragam , jika kita melihat dari grafik peningkatan nilai, mungkin hanya sedikit yang mampu meningkatkan kemampuannya, namun disisi lain , meningkatnya semangat dan penghargaan terhadap pelajaran bahasa inggris ini cukup meningkat, untuk menumbuh kan rasa keingintahuan mereka terhadap bahasa inggris sudah membuat kebanggaan sendiri bagi peneliti.Keywords:  QAR (Question and Answer Relationship), Pemahaman Membaca, Text Deskriptif